Strategic Decisions Without Humans? The Integration of Artificial Intelligence in Management and Accounting - Baihaqi Baihaqi (PT. Hafasy Dwi Nawasena, 2026)
The rapid integration of Artificial Intelligence (AI) into management and accounting has transformed strategic decision-making processes in the era of digital transformation. Organizations increasingly rely on predictive analytics, automated reporting, and real-time decision support systems to enhance efficiency and performance. However, the growing dependence on AI raises critical questions regarding the extent to which strategic decisions can be automated and how professional roles and accountability structures are affected. This study aims to analyze how AI integration reshapes strategic decision-making, particularly in terms of professional role transformation and governance mechanisms. This research employs a qualitative approach using a systematic literature review and thematic analysis of peer-reviewed studies published between 2021 and 2025. Relevant literature on AI, strategic management, management accounting, and digital governance was analyzed to identify recurring themes and structural changes. The findings indicate that AI enhances decision quality, predictive capability, and organizational agility. Nevertheless, AI functions primarily as a decision-support tool rather than a full replacement for human decision-makers. Managerial and accounting roles shift toward strategic interpretation, ethical evaluation, and oversight of AI systems. Governance structures must incorporate transparency, audit mechanisms, and meaningful human oversight to ensure accountability. In conclusion, AI integration produces a hybrid decision architecture in which algorithmic intelligence and human judgment operate collaboratively to maintain legitimacy, accountability, and sustainable organizational performance.